Implementasi Sistem Pertanian Organik di Desa Karangrejo, Kecamatan Gumukmas, Kabupaten Jember: Implementation of Organic Farming Systems in Karangrejo Village, Subdistrict Gumukmas, Jember District - Winarso, Sugeng; Arum, Ayu Puspita; Mandala, Marga; Ma'rufi, Isa; Anggriawan, Rendy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The Mulyo Farmer Group of Karangrejo village are the fostered villages of the University of Jember and have long been food producers, especially rice and corn, with the potential to become one of the providers of organic products according to SNI 6729:2016. Therefore it is essential to evaluate the implementation of gab against the standard requirements of organic farming systems. Some of the activities carried out are Evaluation and increasing understanding of the application of organic farming systems by continuing the practice of making biochar from agricultural waste for long-term organic fertilizer base materials; Focus Group Discussion and ongoing assistance by the Soil Biodiversity and Fertility Research Group UNEJ. The results of the activities show that the community and village officials are thrilled and open to several activities to be carried out. The results of the initial evaluation using the checklist for fulfilling the requirements of SNI 6729:2016 are based on eight variables related to fresh plants and plant products, indicating that there is no program yet to meet the needs of the organic farming system of SNI 6729:2016 or it has not yet been fulfilled. Even though it has not been fulfilled, the potential for implementing it remains open if based on its main potential, namely organic fertilizer sources and water sources (lowlands with relatively shallow groundwater tables). The existence of many livestock and agricultural waste (which is not harvested) available throughout the year can be used as a source of organic fertilizer in maintaining soil fertility or health.